The effects of elevated temperature on the bond between concrete and reinforcing steel bars - Cawood, Robin John (Department of Civil Engineering, 2016)
This investigation forms part of a larger programme undertaken to determine the mechanical, thermal, and time dependent property behaviour of concrete subjected to elevated temperature. A literature review covering the mechanics of bonding, viz. chemical adhesion, frictional effects and mechanical interaction is presented. Parameters which influence bond are discussed. These are properties of the steel reinforcing bar, properties of the concrete, embedment length, casting position of the reinforcing bar and temperature. The research reported herein is primarily concerned with the effects of elevated temperature on the bond between concrete and steel. In this regard, a pullout bond test was used.